Efficient analysis of quasi-optical filters by a hybrid MoM - Bozzi, M. (IEEE Transactions on antennas and propagation)
This paper presents a novel algorithm for the analysis of quasi-optical filters, consisting of thick metal screens perforated periodically with arbitrarily shaped apertures. The algorithm is based on the widely used method of moments (MoM) in conjunction with entire domain basis functions. Its flexibility, accuracy, and rapidity depend on the use of the boundary integral-resonant mode expansion (BI-RME) method in the numerical determination of the basis functions. A computer code has been developed based on this algorithm. The analysis of two different quasi-optical filters operating at 8 GHz and 280 GHz is reported and compared with experimental data as well as with other simulations. In both cases, the whole analysis requires few seconds on a standard workstation and the theoretical results show a very good agreement with the measured data in a wide frequency band. The capability of the MoM/BI-RME approach to handle completely arbitrary shapes is highlighted in the second example. In this case, in fact, the fabrication process causes small deformations of the nominal shape of the apertures, which must be accounted for, since they play an important role in the frequency response of the filter